The development and standardisation of a test of hearing for telephone operators - Raju Ananth (Journal of All India Institute of Speech and Hearing, 1970)
The Government of India had indicated to the All India Instjtute of Speech and Hearing, to dev;develop standardized tests forfixing th~ levels of hearing wnich is essentialfor a telephone operator to perform his dutyefficiently. The problem becomes moreacute when a telephone operator, who isalready appointed dev010ps a h·.Iaring problem.Even during recruitment, no standardisedh aring test has been specified by theGovernment to judge the hearing ~fficiencyof the applican"ts in terms of telephonespeech in trunk exchange environments